The Influence Of Service Quality, Customer Trust, And Customer Satisfaction On Uniqlo's Customer Loyalty - Mutiara Fatihah (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is purposed to examine the relationship between service quality, customer trust, and customer satisfaction on Uniqlo customer loyalty. The analysis unit in this research is the individual, namely customers who have made purchases at Uniqlo more than three times. The data collecting technique in this study were a survey method with the collecting tool being a questionnaire. The results of this study are service quality, customer trust, and customer satisfaction towards customer loyalty.